Iceberg jam floods in Icelandic proglacial rivers: testing the self-organized criticality hypothesis - Roussel, Erwan; Toumazet, Jean-Pierre; Marren, Philip M.; Cossart, Étienne (Géomorphologie : relief, processus, environnement, 2016)
In this paper, we describe a fluvial marginal process associated with the formation of iceberg jams in Icelandic proglacial lakes. The floods triggered by the release of these iceberg jams have implications for the geomorphic evolution of the proglacial fluvial system. The process of iceberg jam floods share some conceptual characteristics with Self-Organized Criticality (SOC) approach of complex systems. Using a simple numerical model and field observations, we test the hypothesis that iceberg jam floods exhibit SOC. Field observations and aerial photo-interpretations in southeastern Iceland demonstrate the occurrence of icebergs jam in ice-contact lakes. The mapping of the south Vatnajökull margins between 2003 and 2012 reveals an increase of the calving potentiality and a rise in the likelihood of iceberg jam flood occurrence. Based on the results of the numerical model and field observations, we suggest that iceberg jam floods should be recognized as a SOC phenomenon. Analysis of the simulated time-series show that the iceberg jam floods become less frequent and more similar in magnitude over time. This global trend is related to the gradual enlargement of the lake outlet channel. Dans cet article, nous décrivons un processus fluvial associé à la formation de barrages glaciels dans les lacs proglaciaires islandais. Les crues déclenchées par la rupture de ces barrages glaciels ont des implications sur l’évolution géomorphologique des systèmes fluviaux proglaciaires. Le processus de crue de barrage glaciel partage des caractéristiques conceptuelles avec l’approche de criticalité auto-organisé (SOC) des systèmes complexes. A l’aide d’un modèle numérique simple et d’observations de terrain, nous testons l’hypothèse de criticalité auto-organisé pour les crues de barrage glaciel. Nos observations de terrain et nos travaux de photo-interprétations aériennes dans le sud de l’Islande témoignent de l’occurrence de barrages glaciels dans les lacs proglaciaires islandais. Le travail de cartographie des marges sud du ...